In vivo inhibition of trypanosome mitochondrial topoisomerase II: Effects of kinetoplast DNA maxicircles - Shapiro, T.A.; Showalter, F. (Informa UK Limited, 1994)
Kinetoplast DNA, the mitochondrial DNA of trypanosomes, is a topologically complex structure composed of interlocked minicircles and maxicircles. We previously reported that etoposide, a potent inhibitor of topoisomerase II, promotes the cleavage of about 20% of network minicircle DNA (T. A. Shapiro, V. A. Klein, and P. T. Englund, J. Biol. Chem. 264:4173-4178, 1989). We now find that virtually all maxicircles are released from kinetoplast DNA networks after trypanosomes are treated with etoposide. As expected for a topoisomerase II cleavage product, the linearized maxicircles have protein bound to both 5' ends. After etoposide treatment, the residual minicircle catenanes have a sedimentation coefficient which is only 70% that of controls, and by electron microscopy the networks are less compact. Double-size networks, the characteristic dumbbell-shape forms that normally arise in the final stages of network replication, are replaced by aberrant unit-size forms.